Coastal Waterbirds Diversity, and Structure under Land Use Changes in the North Coastal of Situbondo, East Java: Coastal Waterbirds Diversity, and Structure under Land Use Changes in the Situbondo Coast, East Java - Kartika Dewi, Yuni; Retnaningdyah, Catur; Setyo Leksono, Amin; Arisoesilaningsih, Endang (Journal of Tropical Life Science, 2025)
Coast is suitable waterbirds habitat, but land use change could negatively influence the waterbirds life. The northern coast of Situbondo Regency, East Java Province, showed variations in land use quality. This study aims to analyze interaction between coastal land use changes on waterbirds diversity and community structure in the coast. Waterbird density was recorded based on the point count along the transect 100 m2 in six stations, namely Kampung Blekok, Tanjung Pecinan, Dubibir, Cemara, Banyuglugur, and Baluran National Park as the reference site. Land use quality in coastal areas was determined by satellites imagery. Habitat preference was determined by neu index. The results showed Tanjung Pecinan and Kampung Blekok stations were favourable waterbirds habitat, dominated by agriculture and low industry areas. These stasions better supported waterbird life and closed characters to Baluran one, where was dominated by mangrove forest and agriculture. This reference site showed highest diversity (H’ 2.26) and evenness (E 0.75), while preference habitat showed lower diversity (H’ 1.39) and evenness (E 0.29). On the contrary, Banyuglugur showed an industrial area, we found a low density species. Baluran and Kampung Blekok were habitat of three IUCN red list species, such as Ciconia episcopus, Charadius javanicus, and Leptoptilos javanicus.